LOCAL SALT BUSINESS DEVELOPMENT STRATEGY IN KEC. BANGKALA District. JENEPONTO - Fitrianti, Nur (Inovbiz: Jurnal Inovasi Bisnis, 2024)
Bangkala District, Jeneponto Regency in Sulawesi South Is an area where salt is one of the businesses that is still being carried out by the surrounding community to this day because the raw materials for producing salt are easy to find, including ponds and brine which are very abundant as the main ingredients for making salt. salt. The local salt business in Bangkala District, Jeneponto Regency, in order to develop, requires the formulation of an appropriate strategy. The purpose of this research is to determine local salt business development strategy in Bangkala District, Jeneponto Regency. This type of research is qualitative research and SWOT analysis. Based on the analysis it was concluded that the strategies that can be used in developing local salt businesses in Bangkala District, Jeneponto Regency First Quality of human resources for salt farmers by providing training on how to produce, digital marketing, and promotion by utilizing social media candone. Second Technology Production can be used to improve quality and quantity of salt Third need the right financing model for salt farmers so that they are no longer constrained by capital in producing salt.